2015
DOI: 10.1080/10410236.2014.944332
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Health Information Among Select Asian American Immigrant Groups in New York City

Abstract: Health information can potentially mitigate adverse health outcomes among ethnic minority populations, but little research has examined how minorities access health information. The aim of this study was to examine variations in the use of health information sources among Asian American (AA) subgroups and to identify differences in characteristics associated with the use of these sources. We analyzed data from a foreign-born community sample of 219 Asian Indians, 216 Bangladeshis, 484 Chinese, and 464 Koreans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…However, there is wide variability in limited English proficiency and linguistic isolation by subgroup. 29 Given inconsistencies observed in prior research based on the acculturation measure applied, 30 our use of a multiitem score may have uncovered health patterns specific to Latinos and Asians. A second and related explanation is that it captured what intersectionality theory suggests: variation in health due to the multiple social positions individuals experience.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is wide variability in limited English proficiency and linguistic isolation by subgroup. 29 Given inconsistencies observed in prior research based on the acculturation measure applied, 30 our use of a multiitem score may have uncovered health patterns specific to Latinos and Asians. A second and related explanation is that it captured what intersectionality theory suggests: variation in health due to the multiple social positions individuals experience.…”
Section: Discussionmentioning
confidence: 99%
“…Mass media plays an important role in disseminating dementia information to the Chinese American general public. While we were unable to quantify the impacts of utilizing an ethnic radio station, previous research has indicated that about 50% Chinese American immigrants used radio to access health information [ 26 ]. This study demonstrates that in addition to obtaining knowledge, community members were willing to call in to a radio show in response to a dementia awareness campaign.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sources of health information vary by the target group (Islam et al, 2016), Internet has often been reported as a popular source of health information across diverse populations (Yoon et al, 2017). With its easy access, anonymity, and language capacity, online health information brings particular benefits to immigrant populations (Wang & Yu, 2015; Yoon et al, 2017).…”
mentioning
confidence: 99%